Creating a historical baseline: economically important alpine plant communities in central Himalaya, Nepal (Botanica Orientalis: Journal of Plant Science, 2020)
There is a lack of historical data on the composition of alpine plant communities in the Himalayas. Such baseline data is essential to understand community dynamics and changes over time. Here, for the first time, we present data and findings on the composition of economically important alpine communities in central Nepal using data from 1994. Lower alpine vegetation on the south-eastern side of Himal Chuli in Gorkha District in central Nepal was phytosociologically examined with particular reference to the occurrence of commercial medicinal and aromatic plants. Eight new plant communities were recognized, comprising five meadow communities and three shrub communities. They were classified into two new groups (higher-ranked syntaxa): lower alpine Rhododendron anthopogon-Bergenia purpurascens shrub found on north-facing slopes and lower alpine Cremanthodium meadows on south-facing slopes. Twelve commercial medicinal and aromatic plant species were found; of main economic importance were Nardostachys jatamansi, Dactylorhiza hatagirea, Aconitum orochryseum, Picrorhiza scrophulariiflora, and Rheum australe. Both north and south-facing communities were important with regard to the collection of plants and income for the local farmers. Harvester risks, e.g. arising from price fluctuations, were reduced with access to many plant communities. Of particular economic importance were the vegetation types Kobresia meadows for the harvest of Nardostachys jatamansi and Cyananthus meadows for the harvest of Dactylorhiza hatagirea.